Quantification of multicellular colonization in tumor metastasis using exome‐sequencing data - Nishino, Jo; Watanabe, Shuichi; Miya, Fuyuki; Kamatani, Takashi; Sugawara, Toshitaka; Boroevich, Keith A.; Tsunoda, Tatsuhiko (International journal of cancer, 2020)
Metastasis is a major cause of cancer‐related mortality, and it is essential to understand how metastasis occurs in order to overcome it. One relevant question is the origin of a metastatic tumor cell population. Although the hypothesis of a single‐cell origin for metastasis from a primary tumor has long been prevalent, several recent studies using mouse models have supported a multicellular origin of metastasis. Human bulk whole‐exome sequencing (WES) studies also have demonstrated a multiple “clonal” origin of metastasis, with different mutational compositions. Specifically, there has not yet been strong research to determine how many founder cells colonize a metastatic tumor. To address this question, under the metastatic model of “single bottleneck followed by rapid growth,” we developed a method to quantify the “founder cell population size” in a metastasis using paired WES data from primary and metachronous metastatic tumors. Simulation studies demonstrated the proposed method gives unbiased results with sufficient accuracy in the range of realistic settings. Applying the proposed method to real WES data from four colorectal cancer patients, all samples supported a multicellular origin of metastasis and the founder size was quantified, ranging from 3 to 17 cells. Such a wide‐range of founder sizes estimated by the proposed method suggests that there are large variations in genetic similarity between primary and metastatic tumors in the same subjects, which may explain the observed (dis)similarity of drug responses between tumors. What's new? The founder cell population size of a metastatic tumor is one of the most important parameters for metastasis dynamics. However, multicellular colonization has not yet been quantified in human metastatic tumors. Using the ‘single bottleneck followed by rapid growth’ metastatic model and whole‐exome sequencing data from primary and metastatic tumors in colorectal cancer patients, this quantification method supports the multi‐cellular origin of metastasis, with founder population sizes ranging from 3 to 17 cells. The wide‐ranging population sizes suggest large variations in genetic similarity between primary and metastatic tumors within individual patients, possibly explaining variations in drug responses between the tumors.